Sources, composition and spatial distribution of marine debris along the Mediterranean coast of Israel. Issue 2 (30th January 2017) - Pasternak, Galia; Zviely, Dov; Ribic, Christine A.; Ariel, Asaf; Spanier, Ehud
Abstract: Marine debris (litter) is a complex problem that affects human activities and the marine environment worldwide. The Clean Coast Program in Israel has had some success in keeping most of the coasts clean most of the time, but without understanding the mechanisms of accumulation of marine debris on the coasts of Israel. In 2012, we initiated a study to characterize the types of marine debris, its origins and spatial distribution. Nineteen surveys were done from June 2012 to March 2015 on eight beaches that spanned the coast of Israel. Average debris density was 12.1 items per 100 m 2 and 90% of the items were plastic. The top debris categories were food wrappers and disposables, plastic bags and cigarette butts. However, there was variation in the top debris categories among the beaches indicating that a flexible approach with multiple options will be important when addressing the marine debris problem. Highlights: The material composition of marine debris in Israel found in the current study is 90% plastic. The average density of marine debris on the Israeli coast 12.1 items/100 m 2 . Most of the debris items found on the Israeli coast was land-based (60%).